Un mois à l’IHEDN : la vision d’une géographe - Marie-Françoise Fleury (Confins)
This text reflects on my participation in the 236th “Grand-Est” regional session of the Institut des hautes études de défense nationale, IHEDN, at the Metz, Reims (in internship), Épinal and Strasbourg sites. It explains how the whole session unfolded, like a field notebook. I describe all the lectures and debates, as well as the visits to military sites, to companies cooperating with the Army and civil security or political centres. The aim is to take stock of the lasting contributions of this immersion to the daily practice of French geography and to understand the intellectual contributions of this session, which complement my university education.